Pelaksanaan Student Centered Learning (SCL) Pembelajaran Bahasa Jawa Di SMK N 3 Klaten (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
The purpose of the research is: (1) describe the implementation of Student Centered Learning in Javanesse language learning at SMK N 3 Klaten; (2) describe the supporting and inhibiting factors in the implementation of Student Centered Learning in Javanesse language learning at SMK N 3 Klaten. This research is an evaluative research with qualitative methods. The data of the research from the process of implementation Student Centered Learning and the data sources from teachers and students. The data collection technique by interview and questionnaires. Analysis techniques using data collection, data display, and conclusion drawing. The research results that the implementation of Student Centered Learning Javanesse language learning has used methods, models, media and learning resources in accordance with Student Centered Learning.The supporting factors in the the implementation of Student Centered Learning is Javanese language teacher. The roles played by the teacher include providing motivation and enthusiasm, providing incentives, and classroom conditioning that can increase the learning activity of students.